2022
DOI: 10.3390/biology11091327
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Selective Signature in Dabieshan Cattle Revealed by Whole-Genome Resequencing

Abstract: Dabieshan cattle are a typical breed of southern Chinese cattle that have the characteristics of muscularity, excellent meat quality and tolerance to temperature and humidity. Based on 148 whole-genome data, our analysis disclosed the ancestry components of Dabieshan cattle with Chinese indicine (0.857) and East Asian taurine (0.139). The Dabieshan genome demonstrated a higher genomic diversity compared with the other eight populations, supported by the observed nucleotide diversity, linkage disequilibrium dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Commercial breeds/populations with a long breeding history, such as East Asian taurine cattle, European taurine cattle and Eurasian taurine cattle, generally have lower nucleotide diversity. At the same time, the nucleotide diversities of North Chinese cattle breeds are all higher than that of these commercial cattle breeds/populations, which is consistent with previous research results (Guan et al., 2022; Li et al., 2023; Liu et al., 2022; Luo et al., 2022; Mei et al., 2018; Xia, Zhang, et al., 2021). In the North Chinese cattle, the nucleotide diversity of Qaidam cattle is higher than that of the other four breeds.…”
Section: Discussionsupporting
confidence: 91%
“…Commercial breeds/populations with a long breeding history, such as East Asian taurine cattle, European taurine cattle and Eurasian taurine cattle, generally have lower nucleotide diversity. At the same time, the nucleotide diversities of North Chinese cattle breeds are all higher than that of these commercial cattle breeds/populations, which is consistent with previous research results (Guan et al., 2022; Li et al., 2023; Liu et al., 2022; Luo et al., 2022; Mei et al., 2018; Xia, Zhang, et al., 2021). In the North Chinese cattle, the nucleotide diversity of Qaidam cattle is higher than that of the other four breeds.…”
Section: Discussionsupporting
confidence: 91%
“…The genomic data could reflect a wide variety of historical developments, including species introductions and artificial selection [26]. The exploration of population genetic structure and genetic diversity can be regarded as essential for genetic evaluation, reflecting cross-breeding and the utilization of genetic resources [27]. In this study, the neighbor-joining tree and PCA analysis showed that the three breeds were clustered by breed.…”
Section: Discussionmentioning
confidence: 80%
“…GPX5 is speci cally expressed in mammalian epididymis and plays an important role in protecting sperm from lipid peroxidation damage, and also affects the fertility rate [50]. In cattle studies, GPX5 GPX6 has also been found to correlate with fertility [51,52].…”
Section: Discussionmentioning
confidence: 99%